The Impact of Effective Governance Systems on the Financial Results of Indonesian Stock Exchange-Listed Manufacturing Firms from 2019 to 2023 - Hidayati, Nur; Rahayu, Heffi Christya; Dewi, Ratna (CV. Strata Persada Academia, 2025)
This study investigates the impact of effective corporate governance mechanisms on the financial performance of manufacturing firms listed on the Indonesia Stock Exchange from 2019 to 2023. Using a quantitative approach, four governance indicators—independent commissioners, audit committees, managerial ownership, and institutional ownership—were analyzed against financial performance measured by Return on Assets (ROA). Data from 21 firms in the consumer goods sector were selected through purposive sampling and analyzed using multiple linear regression. The findings reveal that independent commissioners, audit committees, and institutional ownership positively and significantly influence financial performance. In contrast, managerial ownership shows a significant but negative relationship. The model's adjusted R² value of 0.928 indicates strong explanatory power. These results underscore the crucial role of sound governance structures in enhancing transparency, oversight, and accountability, leading to improved financial outcomes. The study recommends strengthening the functions of independent commissioners and audit committees, encouraging institutional investor involvement, and closely monitoring managerial ownership levels. Future research should explore additional governance variables and broader industry contexts for deeper insights.